2016
DOI: 10.1596/1813-9450-7613
|View full text |Cite
|
Sign up to set email alerts
|

When Do Gender Wage Differences Emerge? A Study of Azerbaijan's Labor Market

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…In a study of US MBAs, Bertrand et al (2010) attribute a growing gender wage gap that increased with age to career interruptions as well as differences in training and weekly hours of work. More recently, similar findings have been noted for several developing countries-see, for example, Pastore (2010) and Pastore et al (2016). This study provides recent evidence for the USA which confirms the existence of much narrower differences in gender wages for younger than older workers.…”
Section: Introductionsupporting
confidence: 88%
“…In a study of US MBAs, Bertrand et al (2010) attribute a growing gender wage gap that increased with age to career interruptions as well as differences in training and weekly hours of work. More recently, similar findings have been noted for several developing countries-see, for example, Pastore (2010) and Pastore et al (2016). This study provides recent evidence for the USA which confirms the existence of much narrower differences in gender wages for younger than older workers.…”
Section: Introductionsupporting
confidence: 88%
“…The sticky floor is a common phenomenon in Asian transition countries. Recent studies on China (Chi & Li, 2008) and Vietnam (Pham & Reilly, 2007; Vu & Yamada, 2018) found a sticky floor effect, while studies on Central Asian transition countries found a sticky floor effect with glass ceiling (Khitarishvili, 2016; Newell & Reilly, 2001; Pastore et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of the sticky floor in China (Chi & Li, 2008) and Vietnam (Pham & Reilly, 2007; Vu & Yamada, 2018). However, evidence from Asian FSU countries indicates that the gender wage gap is higher at both the lower and upper ends of the wage distribution (Newell & Reilly, 2001; Khitarishvili, 2016; Pastore et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a sizeable overall gender wage gap in Azerbaijan's workforce (Pastore et al 2016). Using a unique database from a survey of young people ages 15-29 years shows that new labor market entrants begin with little or no gender differences in earnings, but a wage gap gradually emerges over time closer to the childbearing years.…”
Section: Introductionmentioning
confidence: 99%